Optimizing performance training with a long-term athlete development approach to handball coaches - Listiarini, Dian; Kurniawan, Rian; Shauma, Faizal (Universitas Majalengka, 2024)
Upgrading the competency of existing trainers has not been implemented well and still seems minimal without using sports science studies and approaches. Setting standards and implementing certification of training and upgrading programs is an important element in developing quality handball coaches. Research Objectives to improve the skills of handball coaches, especially those related to the long-term athlete development approach (LTAD). This study was a group pretest-posttest design—45 participants consisting of 12 athletes and 33 physical education teachers. Participants' demographics and outcomes were summarized using descriptive statistics. Pre and post-tests in each group were assessed using paired t-tests. There was a significant increase in the knowledge and skill of handball, knowledge of the training program, and LTAD. This research concludes that coaches can use a long-term athlete development approach to improve handball athletes' skills.